Answer:
3, 6, 9, 12, 15, 18, 21, 24, 27, 30, 33, 36, 39, 42, 45
Step-by-step explanation:
Answer:
96
Step-by-step explanation:
commom difference = d
a₆ + a₇ = 16
a₅ + a₈ = (a₆ - d) + (a₇ + d) = a₆ + a₇ = 16
a₄ + a₉ = (a₆ - 2d) + (a₇ + 2d) = a₆ + a₇ = 16
Similarly,
a₃ + a₁₀ = 16, a₂ + a₁₁ = 16, a₁ + a₁₂ = 16
so
a₁ + a₂ + ... + a₁₁ + a₁₂ = 6 x 16 = 96
Answer:
49×66+49×34 = 49× (66+34)
17X-7Y. You add or subtract the same variables, in this case you only have two x's and one y. So you add them, because you have a addition sign. 13x+4x and you leave the Y alone, because there is not another Y variable.
Answer:
is the solution to the equation: ![4x+12-8x=-1+2x+10](https://tex.z-dn.net/?f=4x%2B12-8x%3D-1%2B2x%2B10)
The statement is true.
Option A is correct.
Step-by-step explanation:
We need to determine if
is the solution to the equation: ![4x+12-8x=-1+2x+10](https://tex.z-dn.net/?f=4x%2B12-8x%3D-1%2B2x%2B10)
Solving the equation first to find value of x
![4x+12-8x=-1+2x+10](https://tex.z-dn.net/?f=4x%2B12-8x%3D-1%2B2x%2B10)
Combining like terms:
![4x-8x+12=2x+10-1\\-4x+12=2x+9](https://tex.z-dn.net/?f=4x-8x%2B12%3D2x%2B10-1%5C%5C-4x%2B12%3D2x%2B9)
Subtracting 2x on both sides
![-4x+12-2x=2x+9-2x\\-4x-2x+12=9\\-6x+12=9](https://tex.z-dn.net/?f=-4x%2B12-2x%3D2x%2B9-2x%5C%5C-4x-2x%2B12%3D9%5C%5C-6x%2B12%3D9)
Now, subtracting 12 on both sides
![-6x+12-12=9-12\\-6x=-3\\](https://tex.z-dn.net/?f=-6x%2B12-12%3D9-12%5C%5C-6x%3D-3%5C%5C)
Divide both sides by -6
![\frac{-6x}{-6}=\frac{-3}{-6}\\x=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-6x%7D%7B-6%7D%3D%5Cfrac%7B-3%7D%7B-6%7D%5C%5Cx%3D%5Cfrac%7B1%7D%7B2%7D)
So, we get
Therefore we can say that
is the solution to the equation: ![4x+12-8x=-1+2x+10](https://tex.z-dn.net/?f=4x%2B12-8x%3D-1%2B2x%2B10)
The statement is true.
Option A is correct.